Prussian blue nanocubes/carbon nanospheres heterostructure composite for biosensing of metformin - Narang J (Dove Medical Press, 2018)
Jagriti Narang,1 Nitesh Malhotra,2 Chaitali Singhal,1 Gajendra Singh,3 Chandra Shekhar Pundir4 1Amity Institute of Nanotechnology, 2Amity Institute of Physiotherapy, Amity University, Noida, Uttar Pradesh, 3Department of Pharmacy, University of Health Sciences, 4Department of Biochemistry, M. D. University, Rohtak, Haryana, India Abstract: This paper reports the fabrication of highly sensitive metformin sensor based on Prussian blue (PB) nanocubes/carbon nanosphere (CNS) heterostructures composed of a perfect cube and spherical composite on a fluorine-doped tin oxide surface. Due to the excellent biocompatibility of PB nanocubes the PB/CNS based Mf sensor exhibited a wide linear range of 0.001–10 mM with a response duration of less than 5 s and a detection limit (based on signal to noise ratio) of 0.1 µM. Keywords: metformin, PB nanocubes, carbon nanospheres, sensor, FTO electrode